Soziogeographische Variation im Deutschen und ihre Übersetzung ins Italienische - Cinato, Lucia (Linguistik Online, 2021)
The translation of multilingual texts, in which diatopic, diastratic and diaphasic varieties contribute to the characterization of the figures and their milieus, poses the problem of the sociolinguistic adequacy of the translation. It is well known that the greatest challenge lies in the varieties caused by the spatial variation of the language, since it is practically impossible to establish perfect equivalence between dialects. However, the reproduction of diamesic varieties, in particular the written reproduction of the spoken language, can cause great difficulties for translators. The article presents the TRADIVARIO project, the aim of which is to investigate strategies and tendencies in the translation of multilingual literary texts for the German-Italian language pair that are characterized by a pronounced sociolinguistic stratification or representative of the variety structure of the spoken language of the present. In addition, the concrete goal of the project is the creation of a parallel corpus as well as the development of a digital platform, which makes the results of the investigation researchable and which can serve as a tool both for translators and learners and as an empirical basis for contrastive linguistic research.